A New Method for Evaluation of Motivational Effects of Drugs - Hidenori Sagara; Hiroaki Araki; Yutaka Gomita (Elsevier, 2012)
Motivation is a process that continuously changes behavior to achieve a goal and can be conceptualized as a series of steps relating to that process. Intracranial self-stimulation (ICSS) behavior is considered to consist of reward and motivational effects. Moreover, priming stimulation of ICSS behavior is known to promote motivational effects. Using the runway method and priming stimulation, rewards and motivational effects of ICSS behavior can be differentiated. We investigated whether the runway method and priming stimulation of ICSS behavior could be used to evaluate motivational effects of a drug. In the ICSS runway model, running speed was considered as a reference of motivational effect. An assessment of pharmacological drugs known to influence motivational states was also undertaken. Using our experimental methods, prominent changes were observed in running speed when animals were administered methamphetamine and nicotine. Based on our results, we conclude that the runway method may be useful for the evaluation of substances that affect motivation. This review introduces 4 types of neuronal processes involved in motivation, reward mechanisms, outlines evaluation methods, and describes motivational properties of psychoactive drugs. Keywords:: intracranial self-stimulation behavior, rewards effect, motivational effect, runway method, priming stimulation